Hubungan Motivasi Dengan Kepatuhan Penggunaan Alat Pelindung Diri Pada Petugas Tpa Raberas Sumbawa Besar - Hasbullah Hasbullah; Rafi’ah Rafi’ah; Nikodimus Margo R (Journal of Educational Innovation and Public Health, 2023)
Garbage is one of the causes of environmental pollution and causes damage to the environment. Waste management purposes to improve public health and environmental quality and make waste a resource. The final waste management site, namely the landfill (TPA), and the role of waste collectors are very much needed in waste management. This study aims to determine the relationship between work motivation and the use of personal protective equipment at TPA Raberas Sumbawa Besar officers. This research is quantitative research with a cross-sectional study method. Data was collected by giving questionnaires and observation sheets to 60 workers at TPA Raberas. The results showed that most respondents had a work motivation of 45 people (75%) following compliance with personal protective equipment; respondents did not comply with 39 people (65.%). Kendall's Tau test results obtained a value of = 0.055. There is no significant relationship between work motivation and the use of personal protective equipment among the TPA Raberas Sumbawa officers. The Kendall's Tau correlation test showed that significant count value > significant table value (0.586> 0.254), then the hypothesis H0 is accepted, and H1 is rejected